Inclusion of children and youth in the Intergovernmental Panel on Climate Change Assessment Reports (AR1-AR6) - Elizabeth Donger; Amiya Bhatia; Joni Pegram; Orla Kelly (Nature Communications)
Abstract Climate change disproportionately impacts the health and wellbeing of children and youth, who are often excluded from climate policy, legislation, and finance frameworks. This article quantifies how frequently children and youth are referenced in the Intergovernmental Panel on Climate Change (IPCC) Assessment Reports (AR1-AR6) and analyses related evidence in AR6. We find references to children and youth in the IPCC reports increased substantially in AR6. The frequency of references varies considerably across Working Group (WG) reports and chapters, with most references appearing in two WG II chapters: ‘Health and Wellbeing’, and ‘Africa’. The vast majority of content on children pertains to climate risks; most commonly to physical health, with few references to other key risks including education, migration and violence. Conversely, the majority of references to youth relate to climate responses, highlighting research on climate activism more often than risks to youth or evidence on procedural inclusion. Relatedly, children are commonly framed as vulnerable and youth as climate activists. This framing obscures the intersectional, complex needs and capabilities of children and youth. To enhance the comprehensiveness of future IPCC reports, there is a critical need for funding and inclusion of more research on climate change, children and youth.